Modernization of Zagreb in the first half of the 20th century through the prism of electrification - Anić, Tomislav, povjesničar (2020)
Based on the current scholarly literature, daily press, and published archival sources, the author has reconstructed the process of modernization of Zagreb through the prism of electrification. After the initial amazement that the public demonstrations of electric power caused, it became an indispensable energy source in everyday use. Ultimately, the amount of its consumption in industry and per capita is an indicator of development in a particular area.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 73-75.
Summary.
Keywords: Elektrifikacija -- Modernizacija -- Periferija; 20. st; Zagreb